New data on the genus Manota Williston (Diptera: Mycetophilidae) from Africa, with an updated key to the species - Hippa, Heikki; Søli, Geir; Kurina, Olavi (Zootaxa, 2019)
A total of 346 male specimens of Manota collected from 13 countries in Africa are studied. They belong to 40 different species including 12 new to science. The new species are: M. burundiensis (Burundi), M. cornuta (Ghana), M. fuscinula (Ghana), M. geniculata (Gabon), M. kirkspriggsi (Madagascar), M. kjaerandseni (Ghana, Côte d’Ivoire), M. leptochaeta (Madagascar), M. limai (São Tomé and Principe), M. oronnai (Nigeria), M. platychaeta (Madagascar), M. polylobata (Nigeria) and M. triseta (Ghana, Guinea). New records of the following 28 species are presented: M. aculifera Hippa & Kurina, 2012 (Ghana), M. afra Hippa & Kurina, 2012 (Ghana, Democratic Republic of Congo), M. clinochaeta Hippa, 2008 (Madagascar), M. clurina Hippa & Kurina, 2012 (Côte d’Ivoire), M. comata Hippa & Kurina, 2012 (Ghana, Guinea, Democratic Republic of Congo, Uganda), M. cultigera Hippa, 2008 (Madagascar), M. dissidens Hippa & Kurina, 2012 (Ghana, Côte d’Ivoire), M. foliolata Hippa & Kurina, 2012 (Cameroon), M. ghanaensis Hippa & Kurina, 2012 (Ghana), M. grootaerti Kurina & Hippa, 2014 (Democratic Republic of Congo), M. katusabei Hippa & Kurina, 2012 (Ghana, Guinea, Uganda), M. lachaisei Matile, 1972 (Democratic Republic of Congo), M. mabokeensis Matile, 1972 (Democratic Republic of Congo, Uganda), M. macrodon Hippa, 2008 (Madagascar), M. mazumbaiensis Søli, 1993 (Ghana, Guinea, Uganda), M. natalensis Jaschhof & Mostovski, 2006 (Republic of South Africa), M. peltata Kurina & Hippa, 2014 (Ghana), M. peltigera Kurina & Hippa, 2014 (Ghana, Uganda), M. petiolata Hippa & Kurina, 2012 (Ghana), M. phyllochaeta Hippa, 2008 (Madagascar), M. pilosa Hippa & Kurina, 2012 (Ghana, Guinea, Côte d’Ivoire, Nigeria), M. pinnata Hippa & Kurina, 2012 (Democratic Republic of Congo), M. pinnulata Hippa & Kurina, 2012 (Ghana), M. reclinata Kurina & Hippa, 2014 (Ghana, Guinea, Côte d’Ivoire), M. relicina Hippa & Kurina, 2012 (Uganda), M. senticosa Hippa & Kurina, 2012 (Ghana, Gabon, Guinea, Central African Republic), M. uncinata Hippa, 2008 (Madagascar) and M. whiteleyi Jaschhof & Mostovski, 2006 (Ghana, Cameroon). An updated key to the Afrotropical Manota species is provided and their distribution briefly discussed. Altogether 68 species of Manota are now known from the Afrotropical region, while the genus holds 314 described species worldwide.